Glibenclamide Is Comparable to Target Temperature Management in Improving Survival and Neurological Outcome After Asphyxial Cardiac Arrest in Rats. Issue 7 (13th July 2016) - Huang, Kaibin; Wang, Ziyue; Gu, Yong; Hu, Yafang; Ji, Zhong; Wang, Shengnan; Lin, Zhenzhou; Li, Xing; Xie, Zuoshan; Pan, Suyue
Abstract : Background: We previously have shown that glibenclamide (GBC), a sulfonylurea receptor 1–transient receptor potential M4 (SUR1‐TRPM4) channel inhibitor, improves survival and neurological outcome after asphyxial cardiac arrest and cardiopulmonary resuscitation (ACA/CPR). Here, we further compare the efficacy of GBC with target temperature management (TTM) and determine whether the efficacy of GBC is affected by TTM. Methods and Results: Male Sprague‐Dawley rats (n=213) subjected to 10‐minute ACA/CPR were randomized to 4 groups after return of spontaneous circulation (ROSC): normothermia control (NT); GBC; TTM; and TTM+GBC. Survival, neurodeficit scores, histological injury, as well as the expressions of SUR1 and TRPM4 were evaluated. The 7‐day survival rate was 34.4% (11 of 32) in the NT group, 65% (13 of 20) in the GBC group, 50% (10 of 20) in the TTM group, and 70% (14 of 20) in the TTM+GBC group. Rats that received either GBC, TTM alone, or in combination showed less neurological deficit than NT control at 24, 48, and 72 hours and 7 days after ROSC. Moreover, TTM or GBC ameliorated neuronal degeneration and glial activation in the hippocampal CA1 region with similar efficacy, whereas the combination of them had a trend toward better effect. The subunits of SUR1‐TRPM4 heterodimers were both strongly upregulated after ACA/CPR and expressed in multiple types of brain cells, but partly suppressed by TTM. Conclusions: GBC is comparable to TTM in improving survival and neurological outcome after ACA/CPR. When GBC is given along with TTM, less histological injury tended to be achieved.